12350 A Rare Case Of Giant Parathyroid Adenoma Managed Medically For 8 Months: A Case Report - Saffi Labram; Luka Bilandzic (Journal of the Endocrine Society, 2024)
Abstract Disclosure: S. Labram: None. L. Bilandzic: None. Background: Single parathyroid adenoma is the most common cause of primary hyperparathyroidism, and is attributed to approximately 85% of cases[1]. However, those classified as giant (weighing over 3.5 g and having a size greater than 2cm2) are exceedingly rare. This reports a rare case of primary hyperparathyroidism caused by giant parathyroid adenoma and details biochemical response following medical and surgical management. Case Report: A 64 year old black female presented with severe abdominal pain, confusion and constipation. Investigations revealed severe hypercalcemia of 17.3 mg/dl with massively elevated parathyroid hormone of 1255 pg/mL. Ultrasound showed a large hypoechogenic lobulated mass inferior to the left thyroid lobe representing a giant parathyroid adenoma. Due to delayed surgery the patient was initially treated medically over the course of 8 months. Over these months she was admitted to hospital 3 times for symptomatic hypercalcemia and received a total of 3 zolendronic acid infusions. Despite this she was unable to achieve long term remission of hypercalcemia. Cinacalcet was added and tolerated at the dose of 30 mg daily. Hypercalcemia improved, but remained elevated at a range of 11-13 mg/dL and the symptoms of brain fog and constipation did not subside entirely. She was eventually able to undergo surgical resection, and a giant parathyroid adenoma weighing 8.9 g was excised. Intraoperative intact parathyroid hormone (IOiPTH) sampling showed > 50% reduction (prior to removal 878pg/mL, 10 minutes after removal 132 pg/ml, 20 minutes after removal 96pg/mL). Pathological review showed an atypical parathyroid tumor. As the tumor lacked invasive growth it did not meet criteria for carcinoma. Conclusions: This is a rare case of primary hyperparathyroidism caused by a giant solitary parathyroid adenoma. The gold standard for management of primary hyperparathyroidism secondary to parathyroid adenoma is minimally invasive parathyroidectomy. However in our case, due to inability to access immediate surgery, challenging and prolonged medical treatment of severe hypercalcemia followed for 8 months. Ultimately, normalization of calcium level was achieved only by surgical intervention. IOiPTH measurements showed appropriate decrease confirmatory for the complete removal of the adenoma. References: 1. Dr Jacqueline Payne (2016). Hyperparathyroidism. [online] Patient.info. Available at: https://patient.info/doctor/hyperparathyroidism-pro#nav-2. 2. Rahim Mahmodlou, Amin Sedokani, Apameh Pezeshk and Bita Najafinejad (2022). Giant parathyroid adenoma: a case report. Journal of Medical Case Reports, 16(1). doi:https://doi.org/10.1186/s13256-022-03401-y. Presentation: 6/2/2024